2015
DOI: 10.5209/rev_rccv.2015.v9.n1.48845
|View full text |Cite
|
Sign up to set email alerts
|

Correlaciones entre la infección por microquistes de S. lamacanis y CK-MB, Ast y LDH alpacas

Abstract: RESUMENEl presente estudio tuvo por objetivo determinar la correlación entre el número de microquistes de S. lamacanis en miocardio (N°Mq) y los niveles de CK-MB, AST y LDH en sangre de alpacas, a fin de usarlos como predictores de salud o grado de infección por sarcocistiosis. Se utilizaron 41 alpacas de raza Huacaya de 3-5 años de edad del matadero Municipal de Huancavelica-Provincia de Huancavelica-Perú, las muestras de sangre se colectaron ante-mortem y las de miocardio post-mortem. El 100 % de los animale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Other authors also found 100% prevalence rates of myocardium of alpacas infected with S. masoni n. sp. "lamacanis" (Guerrero et al, 1967;López-Torres et al, 2015;Lucas et al, 2019a). No in ammatory reaction against the microcysts was observed (Fig.…”
Section: Discussion and Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Other authors also found 100% prevalence rates of myocardium of alpacas infected with S. masoni n. sp. "lamacanis" (Guerrero et al, 1967;López-Torres et al, 2015;Lucas et al, 2019a). No in ammatory reaction against the microcysts was observed (Fig.…”
Section: Discussion and Resultsmentioning
confidence: 97%
“…produces microcysts in cardiac tissue (Lucas et al, 2019a) and skeletal muscle (Moré et al, 2016). The de nitive host of this parasite is still unknown (Moré et al, 2016), although some studies have suggested that canids also play this role (Leguía et Histology is frequently used to diagnose Sarcocystis in muscle tissues (Bucca et al, 2011;Kojouri et al, 2011;López-Torres et al, 2015) as it could provide information such as the level of adaptation of the parasite to its host. For example, Leguía et al (1990) reported that infection of alpacas with microcysts of S. lamacanis produces hemorrhages associated with the presence of schizonts in the vascular endothelium.…”
Section: Introductionmentioning
confidence: 99%
“…Other authors also found 100% prevalence rates of myocardium of alpacas infected with S. masoni n. sp. "lamacanis" (Guerrero et al, 1967;López-Torres et al, 2015;Lucas et al, 2019a). No in ammatory reaction against the microcysts was observed (Fig.…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…produces microcysts in cardiac tissue (Lucas et al, 2019a) and skeletal muscle (Moré et al, 2016). The de nitive host of this parasite is still unknown (Moré et al, 2016), although some studies have suggested that canids also play this role (Leguía et Histology is frequently used to diagnose Sarcocystis in muscle tissues (Bucca et al, 2011;Kojouri et al, 2011;López-Torres et al, 2015) as it could provide information such as the level of adaptation of the parasite to its host. For example, Leguía et al (1990) reported that infection of alpacas with microcysts of S. lamacanis produces hemorrhages associated with the presence of schizonts in the vascular endothelium.…”
Section: Introductionmentioning
confidence: 99%
“…Most Sarcocystis species can be differentiated by the morphological characteristics of their tissue cysts; however, some species may share cyst morphology (Dubey et al 2016). Histopathology is a useful technique to diagnose sarcocystosis (Pritt et al 2008;López-Torres et al 2015) and it can also provide information on the degree of adaptation of the parasite to its host (Rodriguez et al 2023). In recent years, molecular diagnostic methods have been developed and widely applied, being reliable and practical for Sarcocystis species identi cation (Moré et The aim of this study was to identify Sarcocystis spp.…”
Section: Introductionmentioning
confidence: 99%